STAR-AIK Learning for Moral and Spiritual Formation in Islamic Nursing Education - Masrizal; Hengki Nurhuda (Jurusan Tarbiyah,IAIN PALANGKARAYA, 2026)
This study examined the effectiveness of the STAR-AIK (Spiritual-Transformative Active Reflection in Al-Islam and Kemuhammadiyahan Learning) model in strengthening moral competence and spiritual transformation among nursing students in an Islamic higher education institution. A sequential explanatory mixed-methods design was employed. Quantitative data were collected from 35 students enrolled in the Recognition of Prior Learning (RPL) Nursing Program at Universitas Muhammadiyah Tangerang using the Moral Competence Inventory–Islamic Nursing (MCI-IN). Qualitative data were subsequently obtained through in-depth interviews with 10 purposively selected participants. Paired-sample t-test analysis demonstrated a significant improvement in moral competence after the intervention (t(34)=12.47, p<0.001) with a large effect size (Cohen's d=1.42). The greatest improvements occurred in professional accountability and akhlaq-based empathy. Qualitative findings revealed three sequential stages of spiritual transformation: awareness, internalization, and actualization. Participants reconstructed the meaning of nursing practice as an act of worship, integrated Islamic values into their professional identity, and demonstrated greater empathy, responsibility, and ethical commitment in clinical practice. The findings indicate that reflective AIK learning effectively integrates professional competence, moral values, and spiritual consciousness. The STAR-AIK model offers a practical instructional framework for competency-based Islamic nursing education by combining reflective pedagogy, Islamic values, and professional ethics to strengthen students' moral and spiritual development.